2022
DOI: 10.3390/diagnostics12112620
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Function and Iron Loading Status in a Tertiary Center Hemochromatosis Cohort—A Cardiac Magnetic Resonance Study

Abstract: Background: Haemochromatosis (HCH), a common genetic disorder with variable penetrance, results in progressive but understudied iron overload. We prospectively evaluated organ iron loading and cardiac function in a tertiary center HCH cohort. Methods: 42 HCH patients (47 ± 14 years) and 36 controls underwent laboratory workup and cardiac magnetic resonance (CMR), including T1 and T2* mapping. Results: Myocardial T2* (myoT2*), myocardial T1 (myoT1) and liver T2* (livT2*) were lower in patients compared to contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 55 publications
1
1
0
Order By: Relevance
“…The presented analysis showed that the correlations between the iron turnover parameters and echocardiographic indices were relatively weak. These findings align with data from the literature ( 23 , 35 , 36 ) and our previous results, including cardiac magnetic resonance assessments ( 10 , 37 ). There is probably no “direct” relationship between the levels of iron turnover parameters and myocardial function, and myocardial iron overload is not the only mechanism involved in the development of HH cardiomyopathy ( 1 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The presented analysis showed that the correlations between the iron turnover parameters and echocardiographic indices were relatively weak. These findings align with data from the literature ( 23 , 35 , 36 ) and our previous results, including cardiac magnetic resonance assessments ( 10 , 37 ). There is probably no “direct” relationship between the levels of iron turnover parameters and myocardial function, and myocardial iron overload is not the only mechanism involved in the development of HH cardiomyopathy ( 1 ).…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies presented changes in the heart documented on cardiac magnetic resonance (CMR) in patients with beta-thalassemia, most of whom met the current criteria for iron overload in terms of myocardial T2 * < 20 ms ( 40 42 ). HH is not the same iron overload model as beta-thalassemia, which has been documented in our previous study ( 37 ). In all the studied patients with HH, myocardial T2*, T1, and T2* did not fulfill the clinically severe iron overload (20 ms) threshold, which confirms the hypothesis that in modern patients with HH not simple iron storage in the heart could play an essential role in the heart damage process.…”
Section: Discussionmentioning
confidence: 64%